REAKTUALISASI PANCASILA SEBAGAI LANDASAN FILOSOFIS HUKUM NASIONAL - Balya, Humam (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Pancasila as the basis of the state of Indonesia has a fundamental role in shaping the character and direction of nation development, including in the context of law. This study examines the role of Pancasila as the philosophical foundation of national law and how its values are implemented in the Indonesia legal system. Using normative legal research methods with a conceptual approach, this study analyzes how Pancasila functions as the source of all legal sources that animate every legal product and its enforcement in Indonesia. The results of the study show that the implementation of Pancasila values can be seen in various aspects, including the process of forming laws, court decisions, and legal policies. However, the implementation of these values still faces challenges, such as diverse interpretations and inconsistencies in practice. To ensure that the law in Indonesia is not only legally valid but also morally high and in accordance with the culture of the community, it is important to continue to prioritize the values of Pancasila in every aspect of the legal system. Consistency in the application of Pancasila values will help form a just, prosperous, and united society. Thus, Pancasila can be a strong foundation in the development of a just and cultured national law.